Development of technology acceptance model in Iranian banking (Case study: Refah Bank of Semnan province) - Jafar Razmi; Seyed Abdollah Heydaeriyeh; Ali Shahabi (مدیریت صنعتی, 2014)
Development of new technologies is one of the key success factors in most today’s organizations. But this point must also be considered that the acceptance of new technologies does not happen at the moment; it is a process that takes shape over time, and if the usage is repeated, it can be concluded that acceptance has been successful. Besides the systematical review of the researches conducted on technology acceptance model since it’s development by Davis so far in this paper, there has been an effort regarding basic TAM model variables and adding more neglected variables including habit, the ability to use and advertisements, a technology acceptance model has been presented considering social and cultural situation in Iran. A questionnaire was designed to test the assumptions, and after being completed by the staff of information Technology action Refah bank, it was analyzed using fuzzy dematel. Research result shows the fact that continuous use of a technology (like electronic banking) leads to an increase in habit of use that itself results in an increase of usage, indeed there will be a strong reinforcing loop. On the other hand, habit of using previous system (traditional banking) is of the main obstacles to users willing to use new technologies in Iran.